2021
DOI: 10.1002/er.7575
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the effect of temperature on electric power in photovoltaic thermal systems based on natural zeolite plates

Abstract: Summary The present study aims to predict the effect of the panel temperature on the electrical power obtained by the photovoltaic thermal system (PVT) based on natural zeolite plates. It was carried out using the long short‐term memory (LSTM) and multilayer feed forward (MLF) algorithms, which are popular regression‐based deep learning methods. Models have been developed that can predict the effect of temperature on electrical power by using the regression data obtained from experimental measurements on the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Meltek et al proposed a model to predict the effect of the panel electric power of a photovoltaic thermal (PV-T) system using LSTM and MLF. Mean absolute error (MAE), RMSE, MAPE, and R 2 correlation coefficients were used as performance metrics [26].…”
Section: Photovoltaic Performance Analysis Approachesmentioning
confidence: 99%
“…Meltek et al proposed a model to predict the effect of the panel electric power of a photovoltaic thermal (PV-T) system using LSTM and MLF. Mean absolute error (MAE), RMSE, MAPE, and R 2 correlation coefficients were used as performance metrics [26].…”
Section: Photovoltaic Performance Analysis Approachesmentioning
confidence: 99%
“…Bian investigated the physicochemical quality of bruised apple using dielectric properties (Bian et al., 2020). The research results showed that the dielectric characteristic of the fruit changes with moisture content increment, density, and internal quality (Metlek et al., 2021).…”
Section: Introductionmentioning
confidence: 99%